The Role of New Technologies in Myeloproliferative Neoplasms - Giuseppe A. Palumbo; Stefania Stella; Stefania Stella; Maria Stella Pennisi; Maria Stella Pennisi; Cristina Pirosa; Elisa Fermo; Sonia Fabris; Daniele Cattaneo; Alessandra Iurlo (Frontiers in Oncology, 2019)
The hallmark of BCR-ABL1-negative myeloproliferative neoplasms (MPNs) is the presence of a driver mutation in JAK2, CALR, or MPL gene. These genetic alterations represent a key feature, useful for diagnostic, prognostic and therapeutical approaches. Molecular biology tests are now widely available with different specificity and sensitivity. Recently, the allele burden quantification of driver mutations has become a useful tool, both for prognostication and efficacy evaluation of therapies. Moreover, other sub-clonal mutations have been reported in MPN patients, which are associated with poorer prognosis. ASXL1 mutation appears to be the worst amongst them. Both driver and sub-clonal mutations are now taken into consideration in new prognostic scoring systems and may be better investigated using next generation sequence (NGS) technology. In this review we summarize the value of NGS and its contribution in providing a comprehensive picture of mutational landscape to guide treatment decisions. Finally, discussing the role that NGS has in defining the potential risk of disease development, we forecast NGS as the standard molecular biology technique for evaluating these patients.